2015
DOI: 10.1117/12.2082173
|View full text |Cite
|
Sign up to set email alerts
|

Micro-computed tomography (CT) based assessment of dental regenerative therapy in the canine mandible model

Abstract: High-resolution 3D bone-tissue structure measurements may provide information critical to the understanding of the bone regeneration processes and to the bone strength assessment. Tissue engineering studies rely on such nondestructive measurements to monitor bone graft regeneration area. In this study, we measured bone yield, fractal dimension and trabecular thickness through micro-CT slices for different grafts and controls. Eight canines underwent surgery to remove a bone volume (defect) in the canine’s jaw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The alkaline phosphatase activity studies support the concept that collagen together with CS increases the differentiation of osteoblastic Most recently, a novel nanocalcium sulfate (nCS) material fabricated in our laboratory has been shown to have enhanced physical properties, due to its nanosized particles, for osteoconduction and subsequent bone regeneration [11]. The previous studies with this material have shown that nCS particles have a much higher surface area and superior mechanical strength than the traditional calcium sulfate.…”
Section: Alkaline Phosphatase Studiessupporting
confidence: 50%
See 2 more Smart Citations
“…The alkaline phosphatase activity studies support the concept that collagen together with CS increases the differentiation of osteoblastic Most recently, a novel nanocalcium sulfate (nCS) material fabricated in our laboratory has been shown to have enhanced physical properties, due to its nanosized particles, for osteoconduction and subsequent bone regeneration [11]. The previous studies with this material have shown that nCS particles have a much higher surface area and superior mechanical strength than the traditional calcium sulfate.…”
Section: Alkaline Phosphatase Studiessupporting
confidence: 50%
“…Most recently, the nanosized calcium sulfate product, nCS, used in this present study was shown to be an effective material to support in vivo bone regeneration in a canine model of critical mandibular defects [11]. The rationale for coating collagen membranes with nCS is based on characterization of this material as one with higher surface area and superior mechanical strength than the traditional calcium sulfate [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of bone volume changes with micro‐CT has been recently reported, concluding that this method allowed for reliable evaluation of crestal bone changes around dental implants (Beck‐Broichsitter et al., ; De Barros, Novaes, De Carvalho, & De Almeida, ; Khobragade et al., ). Moreover, this technology permits the evaluation of the bone around the whole circumference of the implant (Becker, Klitzsch, Stauber, & Schwarz, ).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to investigate fractal dimension as a scalar metric of noise texture. Previous studies applied fractal dimension as a feature for tissue classification tasks such as carcinoma detection and bone growth assessment . A previous study demonstrated the challenges of estimating the fractal dimension of a texture from a discrete image .…”
Section: Introductionmentioning
confidence: 99%